Animal models for type 1 and type 2 diabetes: advantages and limitations - Singh, Raj; Gholipourmalekabadi, Mazaher; Shafikhani, Sasha H. (Frontiers in Endocrinology, 2024)
Diabetes mellitus, commonly referred to as diabetes, is a group of metabolic disorders characterized by chronic elevation in blood glucose levels, resulting from inadequate insulin production, defective cellular response to extracellular insulin, and/or impaired glucose metabolism. The two main types that account for most diabetics are type 1 diabetes mellitus (T1DM) and type 2 diabetes mellitus (T2DM), each with their own pathophysiological features.T1D is an autoimmune condition where the body's immune system attacks and destroys the insulinproducing beta cells in the pancreas. This leads to lack of insulin, a vital hormone for regulating blood sugar levels and cellular glucose uptake. As a result, those with T1D depend on lifelong insulin therapy to control their blood glucose level. In contrast, T2DM is characterized by insulin resistance, where the body's cells do not respond effectively to insulin, coupled with a relative insulin deficiency. This form of diabetes is often associated with obesity, sedentary lifestyle, and/or genetic factors, and it is managed with lifestyle changes and oral medications. Animal models play a crucial role in diabetes research. However, given the distinct differences between T1DM and T2DM, it is imperative for researchers to employ specific animal models tailored to each condition for a better understanding of the impaired mechanisms underlying each condition, and for assessing the efficacy of new therapeutics. In this review, we discuss the distinct animal models used in type 1 and type 2 diabetes mellitus research and discuss their strengths and limitations.